Dos poros ao sopro: uma crítica ao paradigma identitário - Pacheco, Elizabeth Medeiros (2012)
The research seeks to accommodate, without hierarchy, the resonances between the aesthetic experimentation, the investigations of the physics and the corporal physiology of the affects from a possible dialogue of their speeches. This seems to be a political gamble in the mixing between this fields that arises since the dawn of the XX century with the crisis of fundamentals. The XIX century had already removed God from the monopoly of the Other. Now subatomic physics faces the uncertainty of the substance, and man is more and more dissonant with all the knowledge about himself, since the positive in the field of cognition becomes intolerable in the field of his experience. As the breaking of identity patterns extending from the borders of the countries till the memory of the cells, the differences are no more treated as essences. The difference begins to be addressed as what is produced between the bodies; what become interesting are the processes of differentiation. How to ensure that "ephemeral I will be stronger than everything that the eternal had always been in me? (Lucio Cardoso). This is the most alive question ever, not by the body, but by the thought